2019
DOI: 10.1002/we.2406
|View full text |Cite
|
Sign up to set email alerts
|

Influence of microcylinders with different vibration laws on the flow control effect of a horizontal axis wind turbine

Abstract: Due to the flow separation on the blade of the NREL Phase VI wind turbine, a new flow control technique involving installation of an off‐surface vibrating small structure is proposed. By considering the actual flow condition, fluid‐solid coupling is applied in which two kinds of microcylinder vibration modes are set up, and the aerodynamic performance is numerically studied. The influence of the vibration modes, amplitude, and frequency of the off‐surface vibrating small structure on the aerodynamic performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In the meanwhile, the influence of cylinder vibration (including vibration frequency, vibration amplitude, and vibration frequency) on blade was discussed. 27 The results showed that the wind energy coefficient of the blade equipped with a cylinder in proper vibration was significantly higher than that of the blades with a stationary cylinder. Ebrahimi and Movahhedi 28 placed the various microtabs at 95% chord edge of the blade pressure side, the placement of the microtab, and the change in the height along the blade spreading direction were discussed.…”
Section: Introductionmentioning
confidence: 95%
“…In the meanwhile, the influence of cylinder vibration (including vibration frequency, vibration amplitude, and vibration frequency) on blade was discussed. 27 The results showed that the wind energy coefficient of the blade equipped with a cylinder in proper vibration was significantly higher than that of the blades with a stationary cylinder. Ebrahimi and Movahhedi 28 placed the various microtabs at 95% chord edge of the blade pressure side, the placement of the microtab, and the change in the height along the blade spreading direction were discussed.…”
Section: Introductionmentioning
confidence: 95%
“…The flow separation and boundary layer control are methods aimed at improving an airfoil's aerodynamic performance, increasing the wind turbine's efficiency. In addition, these methods can adjust the wind turbine's aerodynamic load and output power under varying wind speeds and ensure the generator's safety [1].…”
Section: Introductionmentioning
confidence: 99%
“…(2) Passive control techniques that do not require auxiliary power or a control loop, such as slot [13], multi-element airfoil [14][15][16], leading-edge slat [1,17], Gurney flap [18][19][20], self-activated flaps [21], vortex generator [22][23][24], stall strips [25,26], and other airfoil configurations that can delay or even eliminate dynamic stall.…”
Section: Introductionmentioning
confidence: 99%